Model Determinan Perilaku Inovatif pada Mahasiswa yang Berwirausaha - Helmi, Avin Fadilla (Jurnal Psikologi, 2011)
Enterpreneurship has become one of the main pillars for the development of society’s welfare. University students who hold the future generations have a strategic role in becoming futureenterpreneurs. The most dominant character of enterpreneurship is innovative behavior. The innovative behavior determinant model has been developed previously by the author and has beentested with university students in general and university students who were competing in a university students creativity grant competition. In this study, the author wanted to test theinnovative behavior model particularly with university student enterpreneurs. By using this model, a model for developing innovative behavior in university will be able to be developed further. By using a phenomenological method, 10 undergraduate students who were also enterpreneurs in the Program Mahasiswa Wirausaha (Program of Enterpreneur Students) participated in the study. The result was then concluded as an innovative behavior determinant model for student enterpreneurs.The model was different from the general innovative behavior determinant model. The most dominant psychological aspects found in this study were courage in taking risk and persistent highmotivation. Whereas in the process aspect, ‘love’ aspect in doing enterpreneurship was found as influencing the innovative behavior of student enterpreneurs.